Indian Long-term Non-Progressors Show Broad ADCC Responses with Preferential Recognition of V3 Region of Envelope and a Region from Tat Protein - Kulkarni, Archana; Kurle, Swarali; Shete, Ashwini; Ghate, Manisha; Godbole, Sheela; Madhavi, Vijaya; Kent, Stephen J.; Paranjape, Ramesh; Thakar, Madhuri (Frontiers in Immunology, 2017)
HIV-specific antibody-dependent cell cytotoxicity (ADCC) is likely to be important in governing protection from HIV and slowing disease progression. Little is known about the ADCC responses to HIV-1 subtype C. We characterized ADCC responses in HIV-1 subtype C infected Indian subjects with slow disease progression and identified the dominant antigenic regions recognized by these antibodies. ADCC responses were measured in plasma from 34 Long Term Non Progressors (LTNPs), who were asymptomatic and maintained CD4 count above 500 cells/mm3for the last seven years in absence of Antiretroviral therapy (ART), and 58 ART naïve progressors with CD4 count < 500 cells/mm3 against overlapping HIV-1 peptides using a flow cytometry-based antibody-dependent NK cell activation assay. The assay measured CD107a expression on NK cells as a marker of antibody-dependent NK cell activation and IFN- secretion by NK cells upon activation. The ADCC epitopes were mapped using the matrix of overlapping peptides. Indian LTNPs showed higher and broader ADCC responses compared to the progressors. The Env C and Tat-specific ADCC responses were associated with lower plasma viral load whereas the Env C responses were also associated with higher CD4 counts. Five of 10 LTNP responders targeted epitopes in the V3 region (amino acids 288-330) of Env-C. Additionally, three Tat regions were targeted by ADCC antibodies from LTNPs. ADCC responses were associated with slow HIV progression in Indian subtype C infected cohort. The frequently recognized peptides from the V3 loop of Env and the novel epitopes from Tat by the LTNPs warrants further study to understand the role of ADCC responses to these regions in control and prevention of HIV-1 infection